Healthy heart exercises to control blood pressure in elderly with hypertension - Meivi Sesanelvira Achiroh Dinul Islam; Selvina Aryanti (Program Studi Ilmu Keperawatan-fakultas Ilmu Kesehatan Universitas Malahayati, 2026)
Background: Hypertension is a common health problem among the elderly and can lead to serious complications if left uncontrolled. One non-pharmacological effort is healthy heart exercise, which increases blood vessel elasticity, improves circulation, and lowers blood pressure. Purpose: To determine the effect of healthy heart exercise on blood pressure in elderly people with hypertension. Method: This is a pre-experimental study with a time series design. The sample consisted of 23 elderly people selected using a purposive sampling technique. The intervention, which included healthy heart exercise, was conducted over three consecutive days, each lasting 30 minutes. The research instruments used were a mercury sphygmomanometer, a stethoscope, the Healthy Heart Exercise Standard Operating Procedure (SOP), and an observation sheet. Systolic and diastolic blood pressure data were measured daily before and after the intervention. Statistical analysis used a paired-sample t-test. Results: Univariate analysis showed that the mean blood pressure before exercise on the first day was 149.65/89.48 mmHg, on the second day 148.96/88.00 mmHg, and on the third day 146.70/91.04 mmHg. Bivariate analysis showed a significant decrease after exercise, with blood pressure dropping to 145.48/87.30 mmHg on the first day, 145.65/84.52 mmHg on the second day, and 144.09/87.30 mmHg on the third day (p=0.000 <0.05). Conclusion: Elderly can consistently and regularly perform this heart-healthy exercise three times a week to obtain optimal benefits, as a therapeutic modality for controlling blood pressure.